Case report: A case of ocular infection caused by Corynespora cassiicola - Wang, Qin; Wang, Lu; Lian, Lisha; Pu, Xiaofeng; Tang, Lu; Li, Yanmei; Liu, Yuan (Frontiers in Cellular and Infection Microbiology, 2023)
Objective The aim of this study is to identify the pathogen causing ocular infection in a Chinese patient and to describe its morphological characteristics. Methods Samples from the patient’s intraoperative pus were collected for microscopic examination and culture. Morphology and drug sensitivities of the isolated fungus were analyzed. Ribosomal DNA (rDNA) sequencing was performed and blasted in GenBank. Results A strain of fungi was repeatedly isolated from pus samples in different types of medium. No conidia were shown when the isolate cultured on normal PDA medium, whereas pseudoseptate thick-walled conidia were shown when cultured on medium containing leaf leachate. The results of BLAST and phylogenetic trees based on internal transcribed spacer, beta-tubulin, translation elongation factor 1-alpha, and RNA polymerase II gene demonstrated that the isolated fungus was Corynespora cassiicola. Minimum inhibitory concentration results of this organism were as follows: anidulafungin, 0.06 μg/ml; amphotericin B, 0.12 μg/ml; micafungin, 0.06 μg/ml; caspofungin, 0.5 μg/ml; 5-fluorocytosine, >64 μg/ml; posaconazole, 2 μg/ml; voriconazole, 0.25 μg/ml; itraconazole, 0.5 μg/ml; fluconazole, 64 μg/ml. Conclusion The case was infected with Corynespora cassiicola and led to eye suppurative endophthalmitis and blindness. Combined applications of morphological and molecular biology techniques facilitate accurate diagnosis of fungal infections.